A core promoter variant of angiotensinogen gene and interindividual variation in response to angiotensin-converting enzyme inhibitors. (December 2014) - Yu, Huimin; Lin, Shuguang; Zhong, Jiuchang; He, Min; Jin, Lijun; Zhang, Yuqing; Liu, Guozhang
Introduction: The polymorphic angiotensinogen (AGT) gene is one of the most promising candidates for essential hypertension. The aim of this study was to examine the association between the A-6G variant of the AGT gene and the blood pressure response to angiotensin-converting enzyme (ACE) inhibitors in hypertensive subjects. Methods: Five hundred and nine mildly to moderately hypertensive subjects received ACE inhibitors for six weeks after a two-week run-in period. AGT genotyping was performed by direct polymerase chain reaction amplification and deoxyribonucleic acid (DNA) nucleotide sequencing from peripheral blood. Results: The AA genotype, AG genotype, and GG genotype were present in 301 (59.1%), 186 (36.6%), and 22 (4.3%) of patients, respectively. As compared with patients carrying the AA or AG genotype, those carrying the GG genotype had significantly greater reductions in systolic blood pressure, diastolic blood pressure, pulse pressure and mean arterial pressure ( p =0.007, 0.014, 0.027 and 0.005, respectively). Moreover, stepwise multiple linear regression analysis showed that the A-6G genotype was a significant predictor of systolic blood pressure and pulse pressure reductions ( p= 0.040 and 0.019, respectively). Conclusion: Our study indicates that the A-6G variant of the AGT gene may be an important determinant of interindividual variation in the response to ACE inhibitors.